Pengetahuan dan Stigma Keluarga ODHA Terhadap Orang yang Terinfeksi HIV dan AIDS di Kota Kupang - Akuila Didi; Imelda F. E. Manurung; Amelya B. Sir (Journal of Health and Behavioral Science, 2020)
AIDS is a collection of symptoms and infections or syndromes that arise due to damage to the human immune system due to a viral infection. The date from the Kupang City AIDS Commission where HIV cases reached 937 people year 2017, while AIDS cases amounted to 417 people. The purpose of this research is to find out the description of the knowledge of ODHA families towards people infected with HIV and AIDS and to know the description of the stigma of ODHA families towards people infected with HIV and AIDS. This type of research is quantitative descriptive research. The population in this study were 122 families of HIV and AIDS infected with AIDS and all of them were taken as samples using inclusion criteria. Data collection was done by interview. It is recommended for ODHA should not stay away or even discriminate against these family members, they should get support from the family and feel welcome from the family that created it.